2020
DOI: 10.1021/acs.langmuir.0c02265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stabilizing Particle Size on the Structure and Properties of Liquid Marbles

Abstract: A liquid marble (LM) describes a liquid droplet that is wrapped by nonwetting micro-or nanoparticles and therefore obtains characteristics of a solid powder particle. Here, we investigate the effect of the stabilizing particle size on the resulting structure and properties of the LM. We synthesize a series of polystyrene particles with ultrathin coatings of heptadecafluorooctanesulfonic acid-doped polypyrrole with diameters ranging between 1 and 1000 μm by an aqueous chemical oxidative seeded polymerization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…Due to its low luminescence efficiency, PPy materials exhibit NIR light‐to‐heat photothermal property 61–65 . The UV–visible‐NIR spectra measured for the PPy‐BEH grains synthesized at Py/BEHSS molar ratios of 3/2, 3/1, 3/0.5, and 3/0.25 were similar to those reported for PPy materials 66 (Figure 6b) with an absorption band in NIR region.…”
Section: Resultssupporting
confidence: 75%
“…Due to its low luminescence efficiency, PPy materials exhibit NIR light‐to‐heat photothermal property 61–65 . The UV–visible‐NIR spectra measured for the PPy‐BEH grains synthesized at Py/BEHSS molar ratios of 3/2, 3/1, 3/0.5, and 3/0.25 were similar to those reported for PPy materials 66 (Figure 6b) with an absorption band in NIR region.…”
Section: Resultssupporting
confidence: 75%
“…These results indicated that the stability of the LMs against drying increased with the degree of overlap of the plates as the mechanical stability of the LMs increases with an increase of the degrees of steric hindrance and interlocking among the plates. The stability against impact was correlated with the mechanical integrity of the LMs estimated based on the minimum potential energy above which their shapes were destroyed (Em) utilizing a customized drop stability evaluation apparatus 38,46,47 (Table S1, Figure S7). The potential energy (E) was calculated based on the equation 1.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…In all plate systems, polyhedral LMs were formed and an increase of water volume, allowing a larger number of plates to adsorb onto the droplet, increased sphericity. The LMs were stabilized with plate monolayers rather than multilayers, indicating the gravitational force outcompeted plateplate interactions and thus removed plates not in direct contact with the liquid 38 . Due to the gravity effect, the LM shape started to deviate largely from (near)sphere to oblate at and above 50 µL (Note that the capillary length of water is 2.7 mm.…”
mentioning
confidence: 99%
See 2 more Smart Citations